The modeling of the secure intra-layer interaction in wireless computer networks by the facilities of the formal grammars’ and languages’ theory - Печурин, Н. К.; Кондратова, Л. П.; Печурин, С. Н. (Problems of Informatization and Control, 2014)
This way to describe the protocol data units translation in the transition between the PMD and PLCP sublevels of the open systems interconnection reference model physical layer, based on the models of regular grammars and languages, provides an adequate representation of this interaction. There is proposed in order to simulate the safe interaction of these sublevels on considering them as objects interact in a secure information transmission system to apply above model with the easing of restrictions, where production rules are imposed regularity restriction, and they act as components of the asymmetric encryption system feedforward function